Non-neutralizing anti-type I interferon autoantibodies could increase thrombotic risk in critical COVID-19 patients - Framil, Mario; García-Serrano, Lydia; Morandeira, Francisco; Luchoro, Juan Francisco; Antolí, Arnau; Gomez-Vazquez, Jose Luis; Sierra-Fortuny, Àngels; Solanich, Xavier (Frontiers in Immunology, 2025)
During the COVID-19 pandemic, approximately 15% of patients with severe COVID-19 pneumonia were reported to have neutralizing anti-type I interferon (IFN) autoantibodies, which impaired the antiviral response and led to a poorer prognosis. However, the physiological impact of non-neutralizing autoantibodies remains unclear. In our cohort of COVID-19 patients admitted to intensive care, the presence of non-neutralizing anti-type I IFN autoantibodies increased the risk of thrombotic complications, likely via a cytokine carrier mechanism, prolonging the half-life of cytokines and dysregulating vascular endothelial function. Previous studies have associated non-neutralizing anti-type I IFN autoantibodies with an increased risk of cardiovascular complications in autoimmune diseases like systemic lupus erythematosus, but their relevance in infectious diseases remains uncertain. Stratifying anti-type I IFN autoantibodies based on their neutralizing capacity may have clinical significance not only in terms of susceptibility to infectious diseases but also in predicting cardiovascular and thrombotic events.